ANALISIS TINGKAT KEPATUHAN WAJIB PAJAK TERHADAP PENERIMAAN PAJAK BUMI DAN BANGUNAN DIMASA PANDEMI COVID-19 PADA BAPENDA BANDUNG - Atikah Muammalah; Shofie Rachmani Ninditha; Gunardi . (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2021)
This study aims to find out the percentage of the level of taxpayer compliance before and after the Covid-19 Pandemic, based on data on land and building tax revenues contained in the Regional Management and Revenue Agency (BAPENDA) of Bandung City. The data analysis method used is quantitative and qualitative, where data processed from 30 sub-districts in bandung city. The research results of compliance rate peresentase, in 2019 by 89.92% (Obedient) and in 2020 by 101.76% (Very Compliant), so it can be said that the level of compliance from 2019-2020 increased by 11.94%